2013
DOI: 10.1039/c3ra44037k
|View full text |Cite
|
Sign up to set email alerts
|

An enantioselective approach to (−)-aphanorphine featuring a stereoselective oxidative amidation

Abstract: A formal enantioselective synthesis of (2)-aphanorphine (91% ee), that culminates with the preparation of (+)-O-methyl aphanorphine, was achieved. The methodology involves the diastereoselective synthesis of a key 3,5-disubstituted pyrrolidinone intermediate by the intramolecular oxidative amidation of a suitably functionalized a-hydroxy pentenoic acid derivative. A late-stage N-formyl protection, which functions as a latent N-methyl group, is utilized as a simple alternative to a protecting group switch and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…As a possible candidate for bioactivity investigation and an intriguing structure for methodology development, aphanorphine has attracted synthetic chemists’ interest to develop various approaches to its synthesis. These approaches can be generally classified as follows (Scheme ): (1) Friedel–Crafts alkylation of a tertiary carbocation at the C ring with an electron-rich aromatic A ring contributes the largest portion among these approaches. (2) Similar strategies include radical-initiated coupling or Pd-catalyzed Heck reaction of an aryl halide with an olefin or enol at the C ring. (3) Transannular substitution in the benzazepine moiety can produce the B and C ring in one step. With suitable arrangements, intramolecular substitution allows formation of a bicyclo[3.2.1] system from a 7-membered ring intermediate. (4) Preparation of suitable tetraline or dihydronaphthalene derivatives followed by construction of the C ring. In addition, Grainger et al reported a dithiacarbamate initiated radical cyclization to build the B and C ring followed by construction of the aromatic A ring, which does not belong to those shown above .…”
mentioning
confidence: 99%
“…As a possible candidate for bioactivity investigation and an intriguing structure for methodology development, aphanorphine has attracted synthetic chemists’ interest to develop various approaches to its synthesis. These approaches can be generally classified as follows (Scheme ): (1) Friedel–Crafts alkylation of a tertiary carbocation at the C ring with an electron-rich aromatic A ring contributes the largest portion among these approaches. (2) Similar strategies include radical-initiated coupling or Pd-catalyzed Heck reaction of an aryl halide with an olefin or enol at the C ring. (3) Transannular substitution in the benzazepine moiety can produce the B and C ring in one step. With suitable arrangements, intramolecular substitution allows formation of a bicyclo[3.2.1] system from a 7-membered ring intermediate. (4) Preparation of suitable tetraline or dihydronaphthalene derivatives followed by construction of the C ring. In addition, Grainger et al reported a dithiacarbamate initiated radical cyclization to build the B and C ring followed by construction of the aromatic A ring, which does not belong to those shown above .…”
mentioning
confidence: 99%
“…Subsequent Lewis acid catalysed epoxide opening followed by trapping with allylsilane was predicted to lead to 5 with the approach of the allyl nucleophile occurring from the opposite face to the allyl group that is already present. This reaction, which we refer to as a modified Hosomi-Sakurai reaction, 11 has been used in natural product synthesis, 12 but to the best of our knowledge has not been used in the construction of contiguous all-carbon quaternary centres. Alternative approaches to lactam 4 involving the early development of the allyl group in 6 or alkylation of a C11-based ester were explored but were either ultimately unsuccessful or led to significantly longer reaction sequences (data not shown).…”
mentioning
confidence: 99%
“…This reaction was robust and scalable with 62 g of 6 being prepared in a single batch and without the need for purification by column chromatography at any stage. Ketone 6 could be resolved by treatment with (R)-tert-butanesulfinamide (12) to generate the readily separable diastereomeric imines 13 and 14 (Scheme 3). This approach was inspired by the reported resolution of a ketone-containing intermediate en route to epiboxidine.…”
mentioning
confidence: 99%